ANALYSIS PROPOSED STRATEGIC MARKETING INITIATIVES TO ATTRACT GEN Z CUSTOMERS TO PT BANK PERTAMA MASYARAKAT - Kevin Omar Muhammad (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Throughout 2023, PT Bank Negara Indonesia (BNI) achieved a net profit of IDR 209 trillion, marking a 142% increase from the previous year. Despite this notable growth, BNI's profitability remains significantly lower than its competitors, including BCA, BRI, and Bank Mandiri, which achieved profits of IDR 486 trillion, IDR 604 trillion, and IDR 550.6 trillion, respectively. Additionally, BNI’s market capitalization lags behind, at only IDR 165 trillion compared to BCA’s IDR 1,031 trillion. A preliminary study revealed that BNI struggles to attract Gen Z users, primarily due to the perceived complexity and limited functionality of its Mobile Banking services. These challenges underline the need for strategic innovations to strengthen BNI’s competitive position. This study adopts a mixed-methods approach, combining qualitative and quantitative data collection to provide a comprehensive analysis. Structured interviews were conducted with internal stakeholders at BNI to identify internal challenges and opportunities. Simultaneously, survey questionnaires targeting 150 non-customers of BNI were used to gather external insights. The collected data underwent rigorous reliability and validity tests and were analyzed using SWOT and TOWS frameworks to formulate actionable strategies. Key frameworks such as PESTEL, Porter’s Five Forces, and VRIO were also integrated to enhance the analysis. The findings highlight that BNI’s strengths lie in its robust digital infrastructure, extensive physical and digital reach, and strong brand reputation. However, weaknesses include limited differentiation in digital features, high investment costs, and a smaller user base. Opportunities in digital financial services, sustainable finance, and FinTech collaborations can be leveraged to address these weaknesses. Threats such as intense competition and rising customer expectations necessitate operational efficiency and innovation. Based on these insights, targeted strategies were proposed to enhance BNI’s Mobile Banking platform, expand market reach, and optimize customer engagement, positioning BNI as a competitive player in the Indonesian banking sector.